Thermal and energy performance of PET, HDPE, and LDPE melting using a flat-plate heating system - Mahyuddin Mahyuddin; Muhtadin Muhtadin; Muhammad Faisal; Iqbal Iqbal; Hidayatullah Hidayatullah; Erdiwansyah Erdiwansyah (Politeknik Negeri Lhokseumawe, 2025)
The increasing accumulation of plastic waste, particularly polyethylene terephthalate (PET/PETE), high-density polyethylene (HDPE), and low-density polyethylene (LDPE), poses a significant environmental challenge due to their resistance to biodegradation. This study investigates the feasibility of melting these plastics using a low-cost flat-plate heating system maintained at 400 °C under controlled experimental conditions, with periodic stirring to promote uniform heat transfer. The results indicate that for a 0.2 kg sample, the heater consumed 1.157 kW for PET, 1.369 kW for HDPE, and 1.321 kW for LDPE. Complete liquefaction was achieved in 44 minutes for PET and HDPE, and 45 minutes for LDPE. The maximum temperatures reached were 350 °C for PET and LDPE, and 370 °C for HDPE. The overall heat transfer was calculated at 28.98 W. These findings demonstrate that PET offers the most favourable energy–time balance, making it the most suitable candidate for small-scale recycling via this method. Compared to conventional thermal recycling, the flat-plate heating approach is simpler, more affordable, and potentially scalable for community-level applications. However, limitations remain, particularly regarding small batch size (0.2 kg) and the absence of long-term performance testing. This study provides preliminary evidence that flat-plate heating systems could serve as practical alternatives for decentralized plastic recycling, supporting sustainable waste management practices.